Social media popularity: understanding narcissism behaviour among Broadcasting Student in UiTM Rembau / Nabilah Fatin Zulkifee - Zulkifee, Nabilah Fatin (2018)
Narcissism is a feeling when one feels they are better than others. This quantitative study explains the relationship between new media, internet, social media and narcissism. The existence of the internet in the era of globalization creates different attitudes and traits of human beings. This can be seen as day by day internet users are increasingly aggrieved and some of them misuse the internet as well as social media. The younger generation is especially more likely to point to almost everything in social media, they are too fun and do not mind the impression of the coming day. Narcissism is one of the mental illnesses that are also agreed upon by a specialist and this problem should be taken seriously by some parties.